Green bonds for financing renewable energy and energy efficiency in Southeast Asia: A review of policies - Dina Azhgaliyeva; Anant Kapoor; Yang Liu (Asian Development Bank Institute (ADBI), 2020)
Mobilizing private finance for renewable energy and energy efficiency is critical for the Association of Southeast Asian Nations (ASEAN) not only for the reduction of global temperature rise, but also for meeting fast growing energy demand. Two-thirds of green bonds issued in ASEAN countries were used to finance renewable energy and energy efficiency projects. This paper provides a review of green bond issuances and green bond policies in ASEAN countries. Issuance of green bonds in top three green bond issuing countries in ASEAN, i.e., Indonesia, Malaysia, and Singapore, are reviewed in detail. The review of green bond issuance and green bond policies show that green bond policies in ASEAN countries are effective in promoting green bond issuance. However, this does not mean that green bond policies are effective in promoting renewable energy and energy efficiency projects in ASEAN countries. Proceeds of green bonds issued in ASEAN countries can be used for financing projects abroad or refinancing past loans, thus not necessarily promoting green investments in ASEAN countries. This paper provides policy recommendations for promoting renewable energy and energy efficiency financing using green bonds in their countries. To promote renewable energy and energy efficiency, policy makers should consider limiting eligibility criteria in policies supporting green bonds supporting policies, such as green bond grants, to only domestic projects and/or limiting refinancing using green bonds.
Keywords: Q28; Q42; Q48; Q58; G18; 330; Green bonds; sustainable finance; green bond grant; green bond standards; ASEAN; sustainable and responsible investment; green sukuk